Incompliance in use of universal precautions as a safety measure in emergency department - Singh, Somendra Pal; Kumar, Anil; Gupta, Prashant; Gupta, Mohit; Singh, Praveen; Shrivastava, Swadeep (International Surgery Journal, 2016)
Background:Exposure risk of infections to blood borne pathogens while handling the patients of unknown status had been a matter of concern for medical care providers. Incompliance and lag in use of safety measures as universal precautions had been a major risk factor for contact based infections. Despite the availability of detailed guidelines, the knowledge and compliance with standard precautions vary among medical care providers and have been found to be inadequate in both developed and developing countries. The aims and objectives of the study were to observe the compliance in following the protocols and use of universal precautions by emergency medical staff (residents and nursing staff). Methods: Prospective questionnaire based study conducted in emergency department of UP Rural Institute of Medical Sciences and Research, Saifai, Etawah for the duration of 6 months i.e. January 2015 to June 2015. Results:In our study incompliance towards use of eye ware was maximum followed by Handwash. A total fall of 90.09% was noted in lag of use of universal precautions at the end of the study most probably due to daily reminder by questionnaire. Conclusions:Risk of exposure while handling of patients in emergency is a big threat to every medical care providers and it is unfortunate that maximum of these exposures are due to their incompliant behaviour. A simple reminder towards the use of universal precautions can largely prevent exposure based infections.